Training Ship Arrives Here: USS California State is on Cruise of 12,350 Miled - The Herald Miami Florida (The Herald Miami Florida)
After a wallowing trip through rough seas, the 251 foot training ship, USS. California State, is docked at pier 3, Municipal docks, with a complement of 115 California Maritime School cadets; 12 officers and 15 crew members on a four month cruise that will take them 12,350 miles.